Meningkatkan Motivasi Belajar Pada Materi Keberagaman Sebagai Realitas Asali Kehidupan Manusia Dengan Model Pendekatan PBL Pada Siswa Kelas XII IPS SMAN 1 Capkala - Lukas Marianus (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education in Indonesia faces various complex challenges. Therefore, efforts continue to be made by the government, educational institutions and society as a whole to improve access, quality and relevance of education in order to create a young generation that is skilled, competitive and ready to face global challenges. In the context of the Merdeka Curriculum, Catholic religious education in Indonesia focuses on developing students' understanding of religion, moral values ​​and Catholic spirituality. The independent curriculum emphasizes the Pancasila student profile. Students who are accepted to school at SMAN 1 CAPKALA Kasihan are students who are accepted into majors that do not match their initial interests. Based on the problem conditions above, teachers can provide learning experiences by designing the learning process. One learning model that can be applied is Problem Based Learning (PBL) or problem-based learning. The research objectives include (1) to find out how the use of the Problem Based Learning model in increasing learning motivation on diversity material as the original reality of human life using the PBL approach model in class The material of Diversity as the Original Reality of Human Life with the PBL Approach Model for Class , Class X II students of SMA NEGERI 1 CAPKALA can apply the Pancasila student profile of the independence dimension. The type of research used is qualitative with a descriptive approach. Data collection techniques in this research used observation, interviews and documentation. The data analysis technique used consists of data reduction by selecting raw data to be used as information, data presentation, namely presenting data in the form of descriptions, graphs, tables and drawing conclusions by making conclusions from research results referring to the problem formulation. The use of the problem-based learning model according to syntax which includes student orientation towards problems, organizing students to learn, guiding individual and group investigations, developing and presenting results, analyzing and evaluating the problem solving process, effectively helps increase learning motivation on diversity material as the original reality of human life. Using the PBL Approach Model for Class XII IPS Students at SMAN 1 CAPKALA